1995
DOI: 10.1039/ft9959103385
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivity in nitrobenzene-isooctane mixtures of non-critical composition approaching the liquid–liquid coexistence curve

Abstract: Dynamic light-scattering experiments with mixtures of non-critical composition of the nitrobenzene-isooctane system are carried out to obtain information about the temperature and composition dependence of the mutual diffusion coefficient, D. The system has a mixing gap with an upper critical point. It is shown that D decreases in a characteristic way along two pathways in the phase diagram of the system: approaching the temperature of phase separation in a mixture of constant composition or approaching the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 10 publications
3
14
1
Order By: Relevance
“…For “simple” systems the regular solution model (upper critical point) has been used to calculate the temperature and composition dependence of (∂μ i /∂ x i ) P , T . The calculated temperature and composition dependence of the diffusion coefficient is in qualitative agreement with experimental data. ,,, The observed slowing down of the diffusion process in a wide temperature−composition region along the coexistence curve indicates that from a physical point of view the system is “close” to its binodal curve.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…For “simple” systems the regular solution model (upper critical point) has been used to calculate the temperature and composition dependence of (∂μ i /∂ x i ) P , T . The calculated temperature and composition dependence of the diffusion coefficient is in qualitative agreement with experimental data. ,,, The observed slowing down of the diffusion process in a wide temperature−composition region along the coexistence curve indicates that from a physical point of view the system is “close” to its binodal curve.…”
Section: Resultssupporting
confidence: 80%
“…It is well established that the slowing down of the mutual diffusion process approaching the liquid/liquid coexistence curve of systems with a miscibility gap is a system independent phenomenon. [1][2][3][4][5] The data shown in Figure 4 are replotted in the form of isotherms in the upper part of Figure 5 to bring out similarities to results reported by Kato et al for the same system 30 The critical temperature of the system C 12 E 5 /water is about 20 K lower than that of the system C 12 E 6 /water. In the system C 12 E 6 /water Strey et al have carried out temperature jump experiments to study the dynamics of the system.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…It is well established that the mutual diffusion coefficient D at constant composition of binary liquid mixtures with a miscibility gap shows that D decreases approaching the liquid−liquid coexistence curve. This is a material independent property. For a system with a lower critical point the mutual diffusion coefficient decreases with increasing temperature in the vicinity of the binodal curve. Dynamic light scattering experiments with C 12 E 5 /D 2 O mixtures in the vicinity of the lower critical point have shown that this occurs in the “large aggregate” region of the phase diagram in a region close to the T η ,max ( y ) curve shown in Figure .…”
Section: Resultsmentioning
confidence: 99%